(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud is defined as an information processing system that enables flexible utilization of information and communications resources such as information and communications devices, devices and software integrated and shared through information and communications networks in response to changes in User Speed data. Especially in today’s data-intensive environments, enterprises need to efficiently deploy, store, and process Bigdata. The purpose of this study is to analyze and gain insights from cloud service platform technologies. First, we define a technical analysis of cloud service platforms and analyze their characteristics. Then look at the analytics framework, reference models, and market trends for cloud services. To develop a detailed strategy, we will also look at technology trends in IaaS, PaaS, and SaaS, which are key cloud technologies. Finally, these technologies will be integrated to utilize platform technologies and explore the service market. Each IaaS, PaaS and SaaS strategy is designed from the perspective of public and private organizations.